Pisma iz Tokia - Brumen, Polona (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2024)
Through an analysis of primary and secondary sources in the English language, this article aims to shed light on certain characteristics of the International Military Tribunal for the Far East, which convened in Tokyo for two and a half years in the aftermath of World War II. It relies on official, often secret, correspondence from some tribunal members, as their thoughts - expressed to their home institutions - offer an extremely interesting insight into the tribunal’s affairs, its characteristics, intra-state constitution, and the dilemmas faced by the judges when reaching their final decision. Through the tribunal’s multilateral presence and the simultaneous application of elements derived from various legal systems - despite the tribunal’s workings being stipulated by the Charter of the International Military Tribunal for the Far East and existing international law - the judges were unable to detach themselves fully from their own legal traditions. Amid the multi-layered circumstances of prolonged work far from home, this resulted in unexpected entanglements and power struggles on different levels, both among the participants on site and in their relations with leading figures in their home countries. The main effect of this turn of events was a non-uniform final decision: the majority judgement found the 25 accused guilty, condemning seven to the death penalty. From among the 11 senate members, three judges filed a (partial) separate dissenting opinion, while the President eventually filed only a statement disagreeing with some of the penalties. The contribution of this article lies in disclosing the bench’s non-uniformity, since it contests the widespread perception that the trial in question was an "American show".
Keywords: diplomatic correspondence; diplomatska korespondenca; dissenting opinion; international law; International Military Tribunal for the Far East; international relations; ločeno mnenje; mednarodni odnosi; mednarodno pravo; Mednarodno vojaško sodišče za Daljni vzhod